A tribute to the memory of Pavel Evseevich Sobolevskii (1930-2018) - Allaberen Ashyralyev; Abdullah S. Erdogan (E-Journal of Analysis and Applied Mathematics)
This tribute is devoted to Pavel Evseevich Sobolevskii’s lovely memory and gives a summary of his important contributions to mathematics.